Russian Economic Report, No. 22, June 2010 : A Bumpy Recovery - World Bank (Washington, DC, 2017)
Amid heightened global uncertainties, Russia is experiencing a bumpy recovery. Domestic demand is rising, but unemployment remains high, and credit and investment remain limited. The budget has benefited from higher oil prices, but fiscal consolidation remains important in the medium term. Crumbling infrastructure, especially in transport, could hamper the economy's competitiveness and longer-term growth prospects. The debt crisis in Western Europe sharpens the downside risks to global recovery and oil prices. But the effects on Russia are likely to be blunted by its stronger fiscal and debt positions and by limited trade and financial links with the affected countries. Russia is likely to grow by 4.5 percent in 2010, followed by 4.8 percent in 2011, as domestic demand expands in line with gradual improvements in the labor and credit markets. Employment is expected to improve gradually, however, enabling some further reductions in poverty.